Prevalência e fatores associados a sintomas de estresse pós-traumático, depressão e ansiedade em imigrantes haitianos no Rio Grande do Sul - Brunnet, Alice Einloft (2016)
Haitian immigration to Brazil is a recent event that occurs, mostly since the earthquake that struck Haiti in 2010. The associations between migration and mental health have been the focus of many studies, especially in North American and European countries. The impact of migration on mental health is still controversial. Immigrants are frequently exposed to risk factors such as low socioeconomic status, low educational level, and increased psychological distress. Despite such risks, a number of epidemiological studies indicate that immigrants have lower rates of psychiatric disorders than natives. Studies in different backgrounds are needed to better understand the risk and protection factors for mental health problems in this population. This dissertation is composed by two studies, being one systematic review and one empirical study. The systematic review explores PTSD prevalence in migrants with different cultural backgrounds and analyzes evidence about the immigrant paradox. Eight empirical articles reporting PTSD prevalence in migrants were included following the PRISMA statement guidelines. Most studies were conducted in the USA. PTSD prevalence rates varied between 2.6% and 62%. Due to several methodological issues in the few included studies, there is still not enough evidence to provide support for – or against – the immigrant paradox in PTSD research. Prevalence rates are influenced by a complex interaction between risk and protection factors, and migration per se may be a less important factor than the conditions of migration. High rates of PTSD in migrants were found in the studies, what highlights the need of further research with this population, not only with refugees. More studies should investigate the influence of cultural factors on PTSD prevalence in migrants outside of the USA and Europe. The empirical study aimed to investigate the prevalence and factors associated to PTSD, anxiety and depression symptoms in Haitian migrants in southern Brazil. The sample comprises 66 participants selected from four different sites in three cities of a Brazilian southern state. Participants fulfilled a socio-demographic questionnaire, as well as instruments investigating traumatic events, post-migration difficulties and symptoms of PTSD, anxiety and depression. PTSD prevalence in the sample was 9.1%. Depression and anxiety symptoms were in the clinical range in 10.6% and 13.6% of participants, respectively. Linear regression models were utilized to investigate factors associated to PTSD, anxiety and depression symptoms. Number of traumatic events, acculturation difficulties, discrimination and low social support were associated to the investigated mental health disorders. Potential protective factors are discussed. The results point to the importance of public policies to promote better social support for migrants. Providing information to the Brazilian population about migration may improve receptiveness in the host society.